PAROKI BERAKAR LINGKUNGAN: MUPAS II DALAM PERSPEKTIF KONSILI DAN PASCAKONSILI VATIKAN II - Petrus Canisius Edi Laksito (Bahasa Indonesia, 2020)
The Second Pastoral Consultation of the Diocese of Surabaya held on October 18th-20th 2019 declared the Pastoral Strategic Policy of the Diocese of Surabaya for 2020-2030, formulated in these words: “In the spirit of the Basic Direction, the Catholic Church of the Diocese of Surabaya matures lingkungan rooted parishes present in the middle of the society”. This article wants to know in what matters and how strong this Diocese of Surabaya’s Pastoral Strategic Policy is connected to the voices of the pastors of the universal Church, especially those echoed in the doctrine of the Second Vatican Council (1962-1965) and that of the subsequent period. It is hoped that such reflection brought a clearer vision and understanding regarding such an important policy, granted that it will lead the faithful people of the Catholic Church of the Diocese of Surabaya in their pilgrimage to God in this world for the next 10 years. By knowing its connectedness with the voices of the pastors of the universal Church, it is expected that the faithful people of the Diocese of Surabaya would be more aware of the voice of Jesus Christ, the Good Pastor, who himself leads his flock to the green pastures of love shared in faith and hope with peoples they enconter.